A sulphonated carbon dot–chitosan hybrid hydrogel nanocomposite as an efficient ion-exchange film for Ca2+ and Mg2+ removal. Issue 16 (13th April 2016) - Baruah, Upama; Konwar, Achyut; Chowdhury, Devasish
Abstract : A hybrid chitosan-sulphonated carbon dot nanocomposite as a potential ion-exchange film for Ca 2+ and Mg 2+ absorption is reported. Abstract : We have developed a hybrid hydrogel nanocomposite film via conjugation of oxidised carbon dots synthesized from 11-mercaptoundecanoic acid with chitosan. The potential applicability of the film was then successfully tested for the removal of Ca 2+ and Mg 2+ ions from solution.